Pion and proton showers in the CALICE scintillator-steel analogue hadron calorimeter - Bilki, Burak; Briggl, Konrad; Eckert, Patrick; Harion, Tobias; Munwes, Yonathan; Schultz-Coulon, Hans-Christian; Shen, Wei; Stamen, Rainer (Journal of Instrumentation, 2015)
Showers produced by positive hadrons in the highly granular CALICE scintillator-steel analogue hadron calorimeter were studied. The experimental data were collected at CERN and FNAL for single particles with initial momenta from 10 to 80 GeV/c. The calorimeter response and resolution and spatial characteristics of shower development for proton- and pion-induced showers for test beam data and simulations using GEANT4 version 9.6 are compared.